Karakteristik Kulit Kokon Segar Ulat Sutera Liar (Attacus atlas) dari Perkebunan Teh di Daerah Purwakarta - A. Baskoro; A.M. Fuah; D.R. Ekastuti (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2011)
Attacus atlas is known as wild silk moth that produce cocoon, the cocoon produce silk and have a great economics potential. This research was aimed to collect data and information about the cocoon that taken from the tea garden, Purwakarta. Variables measured in this study were cocoon characteristics and morfometrics such as cocoon weight (whole cocoon husk, cocoon husk without floss and floss weight), percentage of cocoon husk without floss weight from whole cocoon husk, percentage of floss weight from whole cocoon husk, cocoon lenght, circumference of cocoon, diameter of cocoon and the cocoon colour. Cocoon wight and the cocoon morfometrics were variable, indicated by the results obtained, such as whole cocoon husk (0.2-1.86 g), cocoon husk without floss (0.14-1.65 g), percentage of cocoon husk without floss weight from whole cocoon husk (42.59-91.09%), floss weight (0.04-0.38 g), percentage of floss weight from whole cocoon husk (8.91-57.41%), cocoon length (3.37-6.81 cm), diameter (anterior, medial and posterior) of cocoon (1.6-2.98 cm; 1.94-3.4 cm; 1.5-2.91 cm), circumference (anterior, medial, and posterior) of cocoon (2.94-8.82 cm; 4.91-10.02 cm; 4.92-8.33 cm) and cocoon colour was classed into three class; light (32 cocoon or 12.8%); medium (170 cocoon or 68%); and dark (48 cocoon or 19.2%). The values of morfometrics of cocoon varies because the observed cocoon is not clearly known whether it is male or female moth.